Misunderstanding of hepatitis C virus (HCV) infection status by non–specialized medical doctors in patients who achieved sustained virologic response to anti-HCV therapy. Issue 9 (September 2022) - Toyoda, Hidenori; Yasuda, Satoshi; Moriya, Akio; Itobayashi, Ei; Uojima, Haruki; Watanabe, Tsunamasa; Atsukawa, Masanori; Arai, Taeang; Ishikawa, Toru; Mikami, Shigeru; Hiraoka, Atsushi; Tsuji, Kunihiko; et al.
Abstract: Introduction: With the increase in the number of patients with sustained virologic response (SVR) in whom hepatitis C virus (HCV) was eradicated by the anti-HCV therapy, there are now many individuals in whom serum HCV RNA is absent despite positive serum HCV antibodies. However, in general clinical practice, HCV infection remains usually screened by measurement of serum HCV antibodies and patients with SVR can be misunderstood regarding HCV infection status. Methods: In the multicenter study, we conducted interviews with administered questionnaires to SVR individuals who had regular hospital visits after SVR. The prevalence of experiencing an incorrect diagnosis of HCV infection after SVR was assessed. Individuals who experienced this misunderstanding were further asked where they experienced it and how it made them feel. Results: In a survey of 2, 246 SVR individuals, 197 individuals (8.8%) were misunderstood as having persistent HCV infection by medical doctors due to positive HCV antibody, despite the absence of HCV viremia. These misunderstandings occurred most prevalently at a private clinic (55.3%). More than half (53.3%) of these individuals felt anxious about their HCV infection with becoming unsure about their HCV eradication status. Conclusions: Misunderstanding HCV status is commonly occurred in SVR individuals. Specialists in hepatology and infectious diseases should broadly emphasize the fact that most patients with HCV antibodies are now HCV-free because of the use of anti-HCV therapy.